Transcriptomic insight into nitrogen uptake and metabolism of Populus simonii in response to drought and low nitrogen stresses. (7th August 2018) - Zhang, Chunxia; Meng, Sen; Li, Mingjun; Zhao, Zhong
Abstract: Understanding the regulation of plant responses to drought and low nitrogen (N) stresses is necessary to improve N use in water-limited lands, maintaining the sustainable and healthy development of ecosystems. In the present study, we investigated morphological, physiological and transcriptome changes in Populus simonii Carr. root responding to long-term drought and low N stresses. Both stresses resulted in lower net photosynthetic rates, chlorophyll content and total dry weight. Transcriptome analysis of fine roots identified 4642 genes that were differentially expressed in response to drought and/or low N stresses. Most ammonium transporters had high transcript abundances in response to drought and/or low N stress; meanwhile the ratio of ammonium to nitrate concentrations was increased under drought condition. Data of N uptakes and metabolism further supported that fine roots under drought stress increased ammonium uptake, and the aspartate-derived amino acid pathway might play a key role in tolerating drought stress in poplar roots. The large-scale dataset in this study presents a global view of the critical pathways involved in drought and low N stress. When linked with physiology and metabolomics data, these results provide new insights into the modulation of N uptake, metabolism and storage, and events within the N-related pathways for transportation, assimilation and amino acid metabolism.